The TGFβ-induced lncRNA TBILA promotes non-small cell lung cancer progression in vitro and in vivo via cis-regulating HGAL and activating S100A7/JAB1 signaling. (28th September 2018) - Lu, Zhiliang; Li, Yuan; Che, Yun; Huang, Jianbing; Sun, Shouguo; Mao, Shuangshuang; Lei, Yuanyuan; Li, Ning; Sun, Nan; He, Jie
Abstract: Long non-coding RNAs (lncRNAs) play critical roles in multiple cellular processes in non-small cell lung cancer (NSCLC); however, the involvement of lncRNAs in the transforming growth factor-beta (TGFβ) signaling pathway, the critical tumor cell epithelial-mesenchymal transition (EMT) and metastasis pathway, remains poorly understood. To address this issue, we compared the lncRNAs expression patterns of NSCLC cells treated with and without TGFβ1 treatment. We observed that one of the most prominent hits, T GFβ -i nduced l ncRNA (TBILA ), promoted NSCLC progression and was upregulated in tumor tissues. Upregulated TBILA promotes human germinal center-associated lymphoma (HGAL) expression by binding to the Smad transcription factor complex, thereby enhancing RhoA activation. In addition, TBILA induces the S100A7-c-Jun activation domain-binding protein 1 (JAB1) pathway by binding to nuclear S100A7 and enhances pro-survival pathways in NSCLC. These findings have provided us with a new perspective regarding the regulation of the TGFβ signaling pathway in NSCLC and suggest that the lncRNA TBILA can serve as a target for anticancer therapies. Highlights: The lncRNA TBILA is directly upregulated by TGFβ/Smad signaling pathway in NSCLC. TBILA is upregulated in NSCLC and promotes tumor cell progression in vitro and in vivo. TBILA enhances RhoA activation via cis-regulating HGAL expression. TBILA promotes the S100A7- JAB1 pathway by binding to nuclear S100A7 protein.